Pelaksanaan Analisis Mengenai Dampak Lingkungan (AMDAL) Di Indonesia Dalam Rangka Penegakan Hukum Lingkungan Hidup - Erviyanti Rosmaida; Irwan Triadi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The general aim of writing this paper is to clarify the implementation of environmental impact analysis (AMDAL) in Indonesia and efforts to overcome various obstacles faced in enforcing environmental laws. The research method used in writing this article is normative legal research, but what is analyzed is not data, but through a case approach method, namely to be able to understand material facts by paying attention to the abstraction of the formulation of facts that occur in environmental law enforcement in Indonesia. Thus, there is a close relationship between analytical methods and problem approaches. The results of the study show that environmental impact analysis is an effective control method. AMDAL is essentially a refinement of a development project planning process. The negative impacts that are often caused by development projects can be minimized with AMDAL. Efforts that can be made to make this happen are by carrying out development that is environmentally friendly, that is, the environment is taken into account from the time the development is planned until the construction is operational. With environmentally friendly development, development can be sustainable. As has been evaluated, the AMDAL process in Indonesia has many weaknesses, including: AMDAL has not been fully integrated in the licensing of a development activity plan, the community participation process has not been fully optimal. Apart from that, there are also various weaknesses in the implementation of AMDAL studies and the methods for preparing AMDAL, especially socio-cultural aspects, are still weak.